Analisis SWOT Pengembangan Bisnis dalam Keputusan Pembelian Konsumen di Usaha Kosmetik Julius Pasar Parluasan Pematangsiantar - Rusdi Hidayat; Acep Samsudin; Naro Laurensia Damanik (Majalah Ilmiah DIAN ILMU, 2022)
The purpose of this research is to analyze and propose a suitable business development for Julius's cosmetic business at Pasar Parluasan, Kota Pematang Siantar. This study uses a quantitative descriptive method that examines the state of the object being perceived (the natural environment), where the researcher is the key instrument. The data collection technique was carried out by triangulation (combined) from various sources, according to research results, the internal strengths of Julius's cosmetics business and the utilization of existing opportunities, even though the business has weaknesses and threats. Seeing Julius Cosmetics' position in quadrant 1 (one), this company has the skills and strengths to take advantage of all opportunities.